2019
DOI: 10.48550/arxiv.1910.05291
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Emergence of Compositional Languages for Numeric Concepts Through Iterated Learning in Neural Agents

Abstract: Since first introduced by [6], computer simulation has been an increasingly important tool in evolutionary linguistics. Recently, with the development of deep learning techniques, research in grounded language learning has also started to focus on facilitating the emergence of compositional languages without pre-defined elementary linguistic knowledge. In this work, we explore the emergence of compositional languages for numeric concepts in multi-agent communication systems. We demonstrate that compositional l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…esis. The machine learning community has also recently shown an increasing interest in applying IL towards emergent communication (Guo et al, 2019;Li & Bowling, 2019;Cogswell et al, 2019;Dagan et al, 2020;Ren et al, 2020). Different from previous works, we believe that IL is an algorithmic principle that is equally applicable to recovering compositional structure in more general tasks.…”
Section: Introductionmentioning
confidence: 99%
“…esis. The machine learning community has also recently shown an increasing interest in applying IL towards emergent communication (Guo et al, 2019;Li & Bowling, 2019;Cogswell et al, 2019;Dagan et al, 2020;Ren et al, 2020). Different from previous works, we believe that IL is an algorithmic principle that is equally applicable to recovering compositional structure in more general tasks.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, research into language emergence and grounding have received increased attention. The former of which raises the question of how to make artificial languages emerge with similar properties to natural languages, or at least 'natural-like' protolanguages, exhibiting compositionality as the primarily-targeted property [4,21,45,60]. Indeed, languages' compositionality has been shown to further the learnability of said languages [34,64,9,45] and promises to increase the generalisation ability of the artificial agent that would be able to wield them.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been shown that emerging languages are far from being 'natural'-like [39,12,13], there are some successful cases demonstrating the emergence of compositional languages and learned representations (e.g. Kottur et al [39], Lazaridou et al [44], Choi et al [15], Bogin et al [7], Guo et al [21], Korbak et al [37], Chaabouni et al [14]), relative to a given standard of compositionality. This paper focuses exclusively on the Straight-Through Gumbel-Softmax (ST-GS) approach proposed by Havrylov and Titov [23], as it supposedly allows a richer signal towards solving the credit assignment problem that language emergence poses since the gradient can be backpropagated from the listener agent to the speaker agent, while, in comparison, it cannot be backpropagated when using more commonly adopted approaches based on REINFORCE-like algorithms [69].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Computational linguists have been researching the emergence of these properties in artificial languages induced by language games [20,39,9,10,40,33,61,41] to better understand the evolution of natural languages. It is only relatively recently that it has also been investigated within the context of deep learning [46,29,45,25,47,7,19,43,21,15,16,49,60,27,50,2,17,3], as the ability to ground into other modalities a natural-like language is thought to be a prerequisite for general AI [69,54,4,18,3].…”
Section: Introductionmentioning
confidence: 99%